The pedagogical potential of producing audiovisual remixes of classical children's tales for the enhancement of dictation and phonemic transcription at university and tertiary institutions - Orta González, María Dolores (2016)
Fil: Orta González, María Dolores. Universidad Nacional de Córdoba. Facultad de Lenguas; Argentina.